2020
DOI: 10.3389/fpsyg.2020.570345
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Staff Turnover of Young Academics: Job Embeddedness and Creative Work Performance in Higher Academic Institutions

Abstract: Young academics have been facing a problem of high turnover rate due to missing links between the institutions’ policies and the performance. This study explores the effect of job embeddedness and community embeddedness on creative work performance and intentions to leave of young teaching staff in academic institutions in Pakistan. In this study, 300 qualified young academics from public and private universities were selected as subjects and asked to complete a questionnaire. Data were collected via mail-surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 48 publications
1
7
0
2
Order By: Relevance
“…Karatepe and Vatankhah [15] demonstrated that JE bolstered cabin attendants' CPERF. Shah et al's [66] research conducted with academicians in Pakistan showed that JE was positively associated with CPERF. Accordingly, we hypothesize: Hypothesis 4.…”
Section: Hypotheses 221 Direct Effectsmentioning
confidence: 99%
“…Karatepe and Vatankhah [15] demonstrated that JE bolstered cabin attendants' CPERF. Shah et al's [66] research conducted with academicians in Pakistan showed that JE was positively associated with CPERF. Accordingly, we hypothesize: Hypothesis 4.…”
Section: Hypotheses 221 Direct Effectsmentioning
confidence: 99%
“…Society has high expectations and requirements for higher education and teachers, and unprecedented vocational academic problems have emerged in the reform of higher education, resulting in some psychological problems of college teachers. The professional academic and psychological status of college teachers have a great practical significance for alleviating their professional academic and improving their psychological status (Treadway et al, 2020).…”
Section: Related Theories Of the Psychological Status Of Teaching Staffmentioning
confidence: 99%
“…In addition, Coetzer et al (2017) clarified that job embeddedness takes into account the large variety of factors that make workers want to stay (Holtom et al, 2008 and. Shah et al (2020); have found that job embeddedness has a close relationship with employees' turnover intentions. Dechawatanapaisal (2017) found that job embeddedness plays an intermediary role that moderates the relationship with the intention to leave.…”
Section: Moderating Variablementioning
confidence: 99%